AB1186 IL-1beta inhibition with canakinumab in patients with systemic juvenile idiopathic arthritis: Efficacy and safety outcomes from a single-dose, placebo-controlled study. (23rd January 2014) - Quartier, P.; Erguven, M.; Horneff, G.; Berkun, Y.; Lheritier, K.; Kim, D.; Abrams, K.; Constantin, T.
Abstract : Background: IL-1β, a key inflammatory cytokine, appears to play a prominent role in systemic juvenile idiopathic arthritis (SJIA). Canakinumab (CAN), a fully human, anti-IL-1β monoclonal antibody selectively binds to IL-1β and inactivates its signaling, thus suppressing inflammation and associated pain. Objectives: To assess the efficacy and safety of CAN in SJIA patients (pts) with active systemic features at enrollment. Methods: In this 4-week randomized, controlled, double-blind study (β-SPECIFIC 1), pts with active signs and symptoms of SJIA were randomized (1:1) to receive a single dose of CAN (4mg/kg) or placebo sc at Day 1. The primary endpoint, proportion of pts achieving an adapted ACRpedi30 criteria (plus absence of fever) at Day 15, has been reported earlier 1 . Secondary endpoints included higher adapted ACRpedi response both at Day 15 and 29, Physician global assessment (PGA) of disease activity (0-100 mm VAS), number of joints with active arthritis, C-reactive protein (CRP), pain intensity (0-100 mm VAS) and overall safety. Results: A total of 84 pts (CAN, n=43; placebo, n=41) were randomized. High discontinuation rate in the placebo group (90.2%) was due to unsatisfactory therapeutic response vs CAN group (14%). CAN provided statistically significant superior response rates vs placebo at all visits for all ACR response levels: at Day 15, ACRpedi 30, 83.7% vs 9.8%; ACRpedi 50, 67.4% vs 4.9%; ACRpedi 70, 60.5% vs 2.4%; ACRpedi 100, 32.6% vs 0, respectively (all p≤0.0001). Furthermore, CAN provided clinically meaningful improvement vs placebo for, PGA of disease activity; number of active joints and CRP as early as Day 3 (Table). Least square means in overall pain intensity were significantly lower in the CAN vs placebo group at Days 15 and 29 (both, p<0.0001). 55.8% pts in the CAN vs 39.0% placebo group had AEs with the most frequently reported AEs being upper respiratory tract infections. No discontinuations occurred due to AEs. 4 pts had serious AEs, 2 in each treatment group: [CAN: varicella, bronchopneumonia (this patient also had MAS); placebo: gastroenteritis, MAS]. Both pts with MAS recovered. No deaths were reported in either treatment group. Conclusions: A single dose of CAN has superior efficacy to placebo in SJIA pts, providing rapid onset of action and robust initial response in majority of pts, while demonstrating an acceptable safety and tolerability profile. References: Ruperto N et al, [abstract] Arthritis Rheum 2011;63 S1030 Disclosure of Interest: P. Quartier Grant/Research support from: Novartis, Consultant for: Novartis, M. Erguven Grant/Research support from: Novartis, G. Horneff Grant/Research support from: Abbott, Pfizer, Consultant for: Abbott, Pfizer, Novartis, Roche, Y. Berkun: None Declared, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, D. Kim Shareholder of: Novartis, Employee of: Novartis, K. Abrams Shareholder of: Novartis, Employee of: Novartis, T. Constantin: None Declared